From urea to urea cocrystals: A critical view of conventional and emerging nitrogenous fertilizer materials for improved environmental sustainability - Mohamed Eisa; Mariana Brondi; Clinton Williams; Reagan Hejl; Jonas Baltrusaitis (Sustainable Chemistry for the Environment, 2025)
Nitrogen (N) is a critical nutrient that is essential for plant growth and sustainable population development. Since the inception of modern fertilizer technology, N has been supplied to the environment via low-stability fertilizer materials which has resulted in very large losses of reactive nitrogen to the environment. These losses have severe impacts on soil, air and surface water locally and result in changes to the ecosystem biodiversity as well as climate globally. Synthesis of nitrogen fertilizer, such as urea, consumes 1–2 % of global energy as well as significant amounts of natural gas. Therefore, it is necessary to improve the stability of fertilizer-N in the environment to decrease their losses and increase N-use efficiency.This work provides a critical evaluation of the current and emerging methods to stabilize urea fertilizers to deliver nitrogen to the environment more sustainably. The emphasis in this review is placed on material chemistry development, such as recent emergence of urea cocrystals that possess reduced solubility and enhanced environmental stability. The materials analysis suggests that future research needs to focus on urea stabilization methods that create partial bonds between the constituents beyond weak molecular interaction. This requires avoiding unsustainable feedstock, such as formaldehyde, or exogenous stabilizing molecules that affect the soil biota, such as urease inhibitors. These developmental products then need to be transformed into thriving technologies to provide high-value fertilizers by decreasing the energy footprint needed to make ammonia, a precursor of urea.